Analysis of design of subway car universal joint - Biriukov, Serhii (Національний технічний університет "Харківський політехнічний інститут", 2025)
This article discusses various designs of universal joints used in the rolling stock of the Kharkiv subway. We also analyse the weaknesses of the coupling design used in the traction drive of unmodernised rolling stock. A comparison of the basic model of the cardan coupling with couplings that have a more promising design for operation in the subway is made.
Keywords: subway; railway; rolling stock; bogie; traction drive; universal joint